Tungau Debu Rumah dan Faktor Risiko yang Terkait Pada Rumah Siswa SDN 001 Buluh Cina Kabupaten Kampar Provinsi Riau - Muhammad Kurnia Caesar; Lilly Haslinda (Jurnal Ilmu Kedokteran, 2020)
House dust mites (HDM) are organism which may be found in people’s houses around the world. House dust mites can live optimally in the house with humidity above 70%. This study aimed to find out the proportion and risk factors of HDM, and also the relationship in the student’s houses of SDN 001 Buluh Cina, Kampar District, Riau Province. This study was an analytical study with cross sectional design and quota sampling method with 70 respondents. Dust samples were collected from bed, sofa/chair, floor, carpet, and ventilation of student’s houses. The data used in this study and transported for direct microscopic examination of the dust. The data on risk factors obtained from questionnaire. Based on microscopic examination, proportion of HDM positive in this study was 47,1%. Risk factors analysis showed that most respondents have private house status (82,9%), good interpretation of frequency of cleaning the bed (54,3%) and area of ventilation (80%), ceramic floor type (68,5%), and  synthetic bed type (78,5%). Analysis of the relationship between the presence of HDM and risk factors showed that there was a significance difference between risk factor type of bed with the presence of HDM (p < 0,05).